VERSIONS ON TEACHING IN RURAL / COUNTRYSIDE CONTEXT OF ARGENTINA AND BRAZIL - María Rosa Wetzel (Universidad Nacional del Nordeste, 2018)
We are facing a story that recovers aspects of a qualitative research developed in schools of Primary Education and Fundamental Education located in rural contexts of the Argentine Republic and Brazil. The investigative itinerary reflects nuances of the ethnographic studies, addresses a study in cases constituted by Immigrant, Indigenous Peoples and the Social Movement of Landless Workers or MST, revealing the way in which knowledge is socially based in multiple or multi-sectioned sections and some simple sections. The different voices of teachers / professors and researchers vindicate the culture of the settlers, by elucidating the knowledge of the rural reality / field with the disciplinary knowledge, estimating in this course the teaching as collective practice of social emancipation.